2009
DOI: 10.1029/2008wr007109
|View full text |Cite
|
Sign up to set email alerts
|

Surface mining and reclamation effects on flood response of watersheds in the central Appalachian Plateau region

Abstract: [1] Surface mining of coal and subsequent reclamation represent the dominant land use change in the central Appalachian Plateau (CAP) region of the United States. Hydrologic impacts of surface mining have been studied at the plot scale, but effects at broader scales have not been explored adequately. Broad-scale classification of reclaimed sites is difficult because standing vegetation makes them nearly indistinguishable from alternate land uses. We used a land cover data set that accurately maps surface mines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…Ferrari et al [41] described the impacts of traditional surface mining as being more similar to urbanization than forest harvesting. Confounding better understanding of the impacts of MTM/VF is that this practice causes structural changes in the catchment (i.e., topography, drainage density) in addition to altering the water budget due to loss of forest and soil compaction during reclamation; MTM activities can result in major changes to headwater topography and drainage network but the implication of a wholesale alteration in catchment structure and land cover is not well understood.…”
Section: Landuse and Land Cover Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrari et al [41] described the impacts of traditional surface mining as being more similar to urbanization than forest harvesting. Confounding better understanding of the impacts of MTM/VF is that this practice causes structural changes in the catchment (i.e., topography, drainage density) in addition to altering the water budget due to loss of forest and soil compaction during reclamation; MTM activities can result in major changes to headwater topography and drainage network but the implication of a wholesale alteration in catchment structure and land cover is not well understood.…”
Section: Landuse and Land Cover Changesmentioning
confidence: 99%
“…Thus, assessing surface impacts can be complicated by legacy subsurface mining. Ferrari et al [41] modeled runoff responses in the George's Creek basin under increasing mining scenarios. Results show that runoff magnitude increases linearly with increasing mining disturbance, a trend that more closely resembled urbanization than deforestation from forest harvesting.…”
Section: Traditional Surface Miningmentioning
confidence: 99%
“…Grasslands resulting from surface mine reclamation have been shown to be fundamentally different from other grasslands in terms of their impact on hydrology (Negley and Eshleman 2006;Ferrari et al 2009;McCormick et al 2009;Zégre, Maxwell, and Lamont 2013;Miller and Zégre 2014;Zégre et al 2014), terrestrial habitat (Weakland and Wood 2005;Wood, Bosworth, and Dettmers 2006;Simmons et al 2008;Wickham et al 2007Wickham et al , 2013, and aquatic ecosystems (Hartman et al 2005;Pond et al 2008;Fritz et al 2010;Pond 2010;Merriam et al 2011;Bernhardt et al 2012;Merriam et al 2013). Negley and Eshleman (2006) found that watersheds affected by mining and mine reclamation produce increased storm run-off and higher peak hourly run-off rates for storm events in comparison with watersheds not affected by mining.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], a paired catchment study of water balances is employed to show changes in the hydrological behavior of a surface mined (and subsequently reclaimed) catchment relative to an adjacent reference catchment. Ferrari et al [6] similarly highlighted the trend towards a flashy hydrograph more indicative of urban catchments than pre-mining conditions in other reclaimed coal mined catchments in Appalachia.…”
Section: Introductionmentioning
confidence: 87%